2009
DOI: 10.1002/ar.20879
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prolactin on the Population of Epithelial Cells From Ventral Prostate of Intact and Cyproterone Acetate‐Treated Peripubertal Rats: Stereological and Immunohistochemical Study

Abstract: The interactions between steroid and nonsteroid hormones in the prostate are of special interest during the growth phase of the gland. The purpose of this work is to study the influence of prolactin (PL), with or without androgenic blockade, on epithelial cells from peripubertal rat ventral prostate. Twenty male peripubertal Sprague-Dawley rats were grouped as controls, or treated with cyproterone acetate (CA), CA plus PL (CA-PL), or PL. The total number (N total) of epithelial cells, and their labeling indice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…This is in line with the results by Gómez et al [49], who showed that chemical castration induced by cyproterone acetate treatment during prepubertal period did not affect cell proliferation and apoptosis. Therefore, it is likely that effects of androgenic blockade during prepubertal period on cell proliferation and apoptosis are transient and are not maintained in adult boar prostate.…”
Section: Discussionsupporting
confidence: 93%
“…This is in line with the results by Gómez et al [49], who showed that chemical castration induced by cyproterone acetate treatment during prepubertal period did not affect cell proliferation and apoptosis. Therefore, it is likely that effects of androgenic blockade during prepubertal period on cell proliferation and apoptosis are transient and are not maintained in adult boar prostate.…”
Section: Discussionsupporting
confidence: 93%
“…Thus these authors proposed that prolactin induced lateral prostatic growth by increasing nuclear AR levels optimizing prostatic response to circulating testosterone. Gomés and coworkers showed an increase in the number of ARpositive cells after treatment with prolactin in non-castrated rats (Gómez et al 2009). Despite the divergent data in the literature, our results pointed out that in the absence of T, prolactin per se is not able to modulate AR expression.…”
Section: Discussionmentioning
confidence: 99%
“…injected for 28 days. The doses of the treatments were based on previous studies reporting the antioxidant actions of the agents (Kumral et al, 2014;Reddy, 2009;Zheng et al, 2004;Wang et al, 2013;Gómez et al, 2009;Mansouri et al, 2013). Following the 28-day treatment period, epileptic seizure was induced by a single-dose of PTZ (45 mg kg −1 ), while the tap water-given control group was injected with saline.…”
Section: Methodsmentioning
confidence: 99%